Does digital awareness dampen misreporting of Covid-19 data? An empirical investigation - Kumari Youkta; Rajendra Narayan Paramanik; Shreya Nupur (Review of Economic Analysis (REA), 2023)
Manipulation of pandemic induced casualty data poses serious threat to globe. This study is an empirical attempt to assess possible factors causing such data fudging. In order to investigate strategic data misreporting by countries, we have employed acclaimed Benford's law on numbers of deaths reported by 129 countries during both waves of pandemic. Finding reveals that alongside factors like degree of democracy, transparency etc., countries with poor digital awareness are subject to greater manipulation of data.
Keywords: D72; P16; I18; 330; Benford's law; Democracy; Data transparency; Digital awareness